Art and illusion a study in the psychology of pictorial representation - Gombrich, E. H. (Ernst Hans) 1909-2001 (Princeton, N.J. Princeton University Press, 1969)
"This book is directed to all who seek for a meeting ground between science and the humanities. Written by a scholar of humanist training, its temper is scientific. Professor Gombrich is concerned with present-day theories of visual perception, information, and learning, and he uses these in scrutinizing history and psychology of pictorial representation. Searching for a rational explanation of the changing styles of art, the author is led to re-examine many current ideas on the imitation of nature, the function of tradition, and other problems. In testing his arguments he ranges wide over the history of art, noticing particularly the accomplishments of those inventors of artistic illusion, the ancient Greeks and the visual discoveries of such masters as Leonardo da Vinci and Rembrandt, as well as the impressionists and the cubists. Yet his main concern is less with the artists than with ourselves, the beholders, and here he seeks to profit from an analysis of humbler pictorial documents and the tricks and inventions of humorists and commercial artists." -- Provided by publisher.
Includes bibliographical references (pages 399-441) and index.
FA-2699g donated by Melba Abela.
Keywords: Art -- Psychology; Visual perception in art; Psychology and art; Optical illusions in art